ANALISIS KINERJA KEUANGAN PEMERINTAH PUSAT SEBELUM DAN SESUDAH KRISIS - , Kurniawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the influence of global financial crisis of 2008 against the central government's financial performance. The global financial crisis is a crisis sparked by the collapse of sub prime mortgage loan in the United States and hit Indonesia since mid- 2008. Government's financial performance is measured based on 17 variables grouped in the financial ratios, those are liquidity, solvency, budget variance, proportionality, and the growth of budget ratio. The data used in this study is the nature of documentary data from the Central Government Financial Statements (LKPP) semesters I and II the period 2006-2007 (before the crisis) and 2009-2010 (after the crisis) and then calculated into percentage of financial ratios. Non-parametric statistical of Wilcoxon Signed Ranks Test is used in testing the hypothesis of partial to the 17 financial ratios that are formulated into 17 research hypothesis (H1-H17). Results of Wilcoxon Signed Ranks Test showed that all tested hypothesis are not proven (H1-H17 rejected), so it was concluded that the government's financial performance after the crisis is not getting better / worse or showed no significant difference compared with before the crisis. This condition is caused by several things, among others, due to the global financial crisis originating from the capital markets derivative products had no real impact on the management of state finances. On the other hand, the policy of fiscal stimulus, the growth of government spending and optimizing the allocation of domestic debt ratio variables have an impact on government finances tend to be similar in both study periods.